Providing inoculum for Didymella bryoniae studies: the effect of light spectrum and storing at low temperature - Virtuoso, M. C. S. [UNESP]; Silva, E. H. C.; Silva, E. M. [UNESP]; Valente, T. S. [UNESP]; Vargas, P. F. [UNESP]; Braz, L. T. [UNESP]; Panizzi, R. C. [UNESP] (Instituto Internacional de Ecologia, 2021)
The in vitro sporulation of Didymella bryoniae is of great importance for studies that require pure inoculum and in large quantities. Thus, the objectives of this study were to identify the best condition for D. bryoniae sporulation combining different light spectra (UV-A or UV-B light, white light, and continuous dark), with distinct culture media (PDA, V8, ML, and PDAB) and, to evaluate fungus’ survivability stored at -20°C over time. The fungus samples were only able to sporulate when subjected to the UV-B light treatment, regardless of the culture medium. The highest appearance of spores conidium type was observed in the PDAB medium, and the lowest production occurred in the ML medium. Reproductive structures, such as perithecia and pycnidia, were observed in all culture media. However, there was considerable variation in the amount of each structure between the different culture media. The ML and V8 media showed a greater number of perithecia and the PDA and PDAB media presented a greater proportion of pycnidia compared to perithecia. The storage duration at -20°C did not affect mycelial growth or mycelial growth rate. In conclusion, the UV-B light is essential for D. bryoniae in vitro sporulation. Moreover, the culture medium composition influences the type of fungal structure produced, as well as spores’ size and quantity. Freezing at -20°C is an efficient technique that can be used to store D. bryoniae for at least five months without loss of viability.

A esporulação de Didymella bryoniae in vitro é de grande importância para estudos que requerem inóculo puro e em grandes quantidades. Assim, os objetivos deste estudo foram identificar a melhor condição para esporulação de D. bryoniae combinando diferentes espectros de luz (luz UV-A ou UV-B, luz branca e escuro contínuo) com distintos meios de cultura (PDA, V8, ML e PDAB) e, avaliar a sobrevivência do fungo armazenado a -20°C ao longo do tempo. As amostras de fungo só esporularam quando submetidas ao tratamento com luz UV-B, independentemente do meio de cultura. Maior aparecimento de esporos do tipo conídio foi observado no meio PDAB, e a menor produção ocorreu no meio ML. Estruturas reprodutivas, como peritécios e picnídeos, foram observadas em todos os meios de cultura. No entanto, houve uma variação considerável na quantidade de cada estrutura entre os diferentes meios de cultura. Os meios ML e V8 apresentaram maior número de peritécios e os meios PDA e PDAB apresentaram maior proporção de picnídeos em relação aos peritécios. A duração do armazenamento a -20°C não afetou o crescimento micelial ou a taxa de crescimento micelial. Em conclusão, a luz UV-B é essencial para a esporulação de D. bryoniae in vitro. Além disso, a composição do meio de cultura influencia o tipo de estrutura fúngica produzida, bem como o tamanho e a quantidade dos esporos. O congelamento a -20°C é uma técnica eficiente que pode ser usada para armazenar D. bryoniae por pelo menos cinco meses sem perda de viabilidade
Fornecendo inóculo para estudos de Didymella bryoniae: o efeito do espectro de luz e armazenamento em baixa temperatura
Keywords: fungi preservation; gummy stem blight; sporulation; UV-B light; Preservação de fungos; crestamento gomoso do caule; esporulação; Luz UV-B